2016
DOI: 10.1007/s11120-016-0233-2
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable heterologous production of terpene hydrocarbons in cyanobacteria

Abstract: Cyanobacteria can be exploited as photosynthetic platforms for heterologous generation of terpene hydrocarbons with industrial application. However, the slow catalytic activity of terpene synthases (k = 4 s or slower) makes them noncompetitive for the pool of available substrate, thereby limiting the rate and yield of product generation. Work in this paper applied transformation technologies in Synechocystis for the heterologous production of β-phellandrene (monoterpene) hydrocarbons. Conditions were defined w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(97 citation statements)
references
References 37 publications
4
93
0
Order By: Relevance
“…In addition, short regulatory RNAs, like anti‐sense RNAs, might have potential to be developed to tightly controlling regulatory systems for induced protein production (Higo et al ). Furthermore, fast and ‘smooth’ translation has shown to enhance productivity (Formighieri and Melis , Formighieri and Melis ).…”
Section: Beyond Transcription: Regulated Translation and Other Producmentioning
confidence: 99%
“…In addition, short regulatory RNAs, like anti‐sense RNAs, might have potential to be developed to tightly controlling regulatory systems for induced protein production (Higo et al ). Furthermore, fast and ‘smooth’ translation has shown to enhance productivity (Formighieri and Melis , Formighieri and Melis ).…”
Section: Beyond Transcription: Regulated Translation and Other Producmentioning
confidence: 99%
“…Standardised cloning methods, like shotgun cloning or cDNA cloning [110], have been employed to express exogenous genes or knockout native genes in Synechocystis 6803 [111,112,113,114,115,116]. For maximum expression levels of heterologous genes, codon optimisation has been utilised in several studies with favorable effects [16,116,117,118]. Additionally, the development of degradation tags used for the fine-tuning of protein levels and protein turnover times in this model organism have also been achieved [100].…”
Section: Emerging Synthetic Biology Technologiesmentioning
confidence: 99%
“…The expression of ipi , crtR , and crtP and crtB led to a large increase in the corresponding transcript levels that led to the accumulation of zeaxanthin and myxoxanthophyll in the mutant strains [101]. A study involving increased production of carotenoids from Synechocystis 6803 reported a β-phellandrene yield reaching 1% of the dry cell weight [116]. This was accomplished by expressing β-phellandrene synthase as a fusion protein with the β-subunit of phycocyanin.…”
Section: Emerging Synthetic Biology Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pichia pastoris, as a convenient production system of yeast that could heterologously express proteins in high amounts, has been wildly used as a heterogeneous expression system Zhao et al, 2015). To satisfy the strong demand for the thermostable hydrolase production in enzyme preparation industry, heterologous expression using P. pastoris has become the primary way which significantly improves the protein expression level (Formighieri and Melis, 2016). However, as a significant part of glycoside hydrolases of thermophilic C. thermophilum, there are few reports about the thermostable GH6 cellobiohydrolases from C. thermophilum.…”
Section: Introductionmentioning
confidence: 99%